Dspace DS1104 implementation of a robust nonlinear controller applied for DFIG driven by wind turbine. (March 2020) - Mensou, Sara; Essadki, Ahmed; Nasser, Tamou; Idrissi, Badre Bououlid; Ben Tarla, Lahssan
Abstract: This research paper deals whit the control of a doubly fed induction generator (DFIG) driven in rotation by wind turbine, the objective of this work is to control the electromagnetic torque of the generator and have a specified reactive stator power generated whatever perturbations, the MPPT method was used to extract the maximum of the power for different wind speed variations. To control the system studied we have used the Nonlinear Backstepping Controller with Lyapunov function, the robustness of our controller is tested in terms of reference tracking under perturbed conditions (generator parameters variations and voltage dips). All were implemented on dSPACE DS1104 Controller card Real-Time Interface (RTI), which runs in Simulink/MATLAB environment and ControlDesk 4.2 graphical interfaces. Hardware simulation results show and validate the performances and robustness of our controller. Highlights: The Wind Turbine is modelled and simulated with a variable wind speed operation. The control of the DFIG is adopted to extract the maximum of the power. The robustness and performance of our controller is tested under disturbances. The proposed control method is implemented in real-time using dSPACE control board.